Analisis Ketidakharmonisan Rumah Tangga Sebagai Alasan Utama Perceraian - Rezki Pulungan, Nita Nilan Sry; Dinda Adistya Nugraha; Annisa Hafizah; Lubis, Aldi Subhan (Universitas Medan Area, 2026)
This research discusses marital disharmony, with the main objective of identifying the factors that cause disharmony in households that become primary grounds for divorce, as well as the efforts that should be undertaken to suppress the increasing rate of divorce. The research method used is normative legal research, focusing on the study of legal documents, legal theories, and statutory regulations. The findings show that various factors contribute to marital disharmony, including lack of effective communication between spouses, differences of opinion in various matters, economic problems, infidelity, and egoism, all of which may lead to family breakdown and even divorce. The divorce rate in the city of Medan has increased, indicating that many households experience conflict and do not function as they should. Internal efforts include prioritizing religious values within the family, maintaining good communication between husband and wife, mutual respect and forgiveness, showing appreciation for one another, and giving each partner personal space. External efforts include government initiatives such as establishing the Marriage Advisory, Development, and Preservation Agency (BP4), Marriage Guidance programs (Bimwin), and pre-marital and post-marital counseling services organized by the Office of Religious Affairs (KUA), as well as the Ministry of Religious Affairs facilitating the provision of self-guidance manuals.